If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2.7t = 4.8t + -9 Reorder the terms: 9 + 2.7t = -9 + 4.8t Solving 9 + 2.7t = -9 + 4.8t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4.8t' to each side of the equation. 9 + 2.7t + -4.8t = -9 + 4.8t + -4.8t Combine like terms: 2.7t + -4.8t = -2.1t 9 + -2.1t = -9 + 4.8t + -4.8t Combine like terms: 4.8t + -4.8t = 0.0 9 + -2.1t = -9 + 0.0 9 + -2.1t = -9 Add '-9' to each side of the equation. 9 + -9 + -2.1t = -9 + -9 Combine like terms: 9 + -9 = 0 0 + -2.1t = -9 + -9 -2.1t = -9 + -9 Combine like terms: -9 + -9 = -18 -2.1t = -18 Divide each side by '-2.1'. t = 8.571428571 Simplifying t = 8.571428571
| 8x-3y=-24 | | x-4+99=8 | | 4-7x=3x+1 | | 3x+47=7x+10 | | 12x-24-8x=-6x+16 | | 5x+13-4x=7+4x-6 | | 3x+14=85-8x | | 1/4=z+7/4 | | 14x+120+10x=360 | | 3[6x-4]=-52 | | 4+7(-12+x)=-38 | | 24+14x=x | | 3y+z=am | | [6x-4]=-52 | | 4x-10=6x+12 | | 14x+24=x | | 6x-4=-52 | | 6x-7=5x+6 | | 8x-1=8x-x | | 6x+8x=x | | -9=x+12 | | 3x+5x-15=37 | | 7x+1=7x-x | | a(b-c)=d | | x+108=100 | | 8+4d=36 | | 18+108=126 | | 8+4d=37 | | z=6*3.14xy | | 2-11x=122+x | | 20+3n=-4 | | -9x-4=23 |